Democratic education: Comparative book review of two handbooks - Grammes, Tilman (JSSE - Journal of Social Science Education, 2024)
Wolfgang Beutel, Markus Gloe, Gerhard Himmelmann, Dirk Lange, Volker Reinhardt, & Anne Seifert (Eds.). (2022). Handbuch Demokratiepädagogik [Handbook on democratic education] Frankfurt/Main: Wochenschau. ISBN: 9783954141869. Julian Culp, Johannes Drerup, & Douglas Yacek (Eds.). (2023). The Cambridge handbook of democratic education. Cambridge: Cambridge University Press. ISBN: 9781009071536. https://doi.org/10.1017/9781009071536